A design alchemist - Mallebranche, Sophie (Base Diseño e Innovación, 2015)
Sophie Mallebranche transmutes metal into textile. A weaving process that turns alloys and minerals into sources of multicolor light, creating a magic effect in both indoor and outdoor environments.